Penerapan Pendekatan Andragogi dalam Pembelajaran Partisipatif pada Program Paket C di PKBM Miftahun Najah - Bella Ayu Pratiwi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Non-formal education offers an alternative route for learners who have not completed formal schooling, particularly at the secondary level. In Indonesia, the Equality Education serves as this pathway, targeting adult learners with varied life experiences and learning needs. The effectiveness of the program depends largely on the learning approaches employed, especially participatory methods that align with andragogical principles. This study examines how an andragogical approach is implemented in participatory learning activities within the Equality Education PKBM Miftahun Najah, Banyuwangi Regency. A qualitative descriptive design was applied, with data collected through observations, interviews, and document analysis involving tutors and learners. The analysis focused on three core andragogical assumptions proposed by Knowles: the need to know, self-concept, and learners’ experiences, which closely relate to participatory learning practices. Data were analyzed through stages of reduction, presentation, and conclusion drawing. Findings indicate that andragogical principles are present in participatory learning, although their application is not fully integrated across all stages. Learner engagement improved when activities were contextual, practice-oriented, and connected to everyday experiences, particularly in empowerment programs such as coffee processing. Participants’ experiences were actively used as learning resources through discussion and experience sharing. Nonetheless, learner involvement in planning and evaluation remained limited, with some participants exhibiting passive behavior during classroom sessions. In conclusion, the andragogical approach contributes positively to participatory learning; however, further efforts are needed to enhance learner engagement, strengthen tutors’ competencies in adult learning strategies, and ensure more consistent participatory practices.
:: Finalisasi file repositori 4 Agustus 2026_Kurnadi
Keywords: adult learners; andragogy; non-formal education; participatory learning; Equality Education Program.